A prevalence study of children with imprisoned fathers: annual and lifetime estimates. Issue 3 (September 2013) - Dennison, Susan; Stewart, Anna; Freiberg, Kate
Abstract : In Australia, data are not routinely collected on the parental status of prisoners, so there are no official nationwide figures and few State‐based figures. The current study uses data collected in Queensland over a six‐month period to estimate how many Queensland children, in one year and in their entire childhood, experience paternal imprisonment. Additional data were collected relating to the provision of care for the child prior to, and during, their father's imprisonment. Participants were 303 imprisoned fathers (51 per cent of Aboriginal and/or Torres Strait Islander origin) who reported a total of 753 children. Using these data and population statistics, it was estimated that 0.8 per cent of children in Queensland experienced paternal imprisonment in one year while approximately four per cent experience paternal imprisonment in their lifetime. Indigenous children were nine times more likely to experience paternal imprisonment in one year and four times more likely to experience paternal imprisonment in their lifetime compared to non‐Indigenous children. Approximately half of the children (48 per cent) lived with their father prior to his imprisonment. Results are discussed in relation to whether children were living with their father as well as the possibility of pre‐existing risks in children's lives that may subsequently interact with their father's imprisonment.